2019
DOI: 10.1101/860668
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

17q21.31 sub-haplotypes underlying H1-associated risk for Parkinson’s disease are associated with LRRC37A/2 expression in astrocytes

Abstract: Parkinson's disease (PD) and progressive supranuclear palsy (PSP) are clinically similar neurodegenerative movement disorders that display unique neuropathological features (i.e. Lewy body pathology and Tau pathology, respectively). While each disorder has distinct clinical and genetic risk factors, both are associated with the MAPT 17q.21.31 locus H1 haplotype. This suggests a pleiotropic effect of this genomic region. To better understand the genetic contribution of this region to these diseases, we fine-map… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 111 publications
1
3
0
Order By: Relevance
“…The exact function of these genes remains to be elucidated, but presumably, they play a role in cellular migration, chemotaxis, and immunity. 48 , 49 Similar to our findings, evidence from several studies indicates that 17q21.31-inv is significantly associated with the expression levels of LRRC37A4P , A2, and A1 in adult samples 9 , 46 , 48 , 50 and fetal brains. 51 , 52 In short, these findings suggest that the inversion has a significant impact on gene regulation.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The exact function of these genes remains to be elucidated, but presumably, they play a role in cellular migration, chemotaxis, and immunity. 48 , 49 Similar to our findings, evidence from several studies indicates that 17q21.31-inv is significantly associated with the expression levels of LRRC37A4P , A2, and A1 in adult samples 9 , 46 , 48 , 50 and fetal brains. 51 , 52 In short, these findings suggest that the inversion has a significant impact on gene regulation.…”
Section: Resultssupporting
confidence: 91%
“… 46 , 47 Further, we observed and replicated the significance and effect direction of several LRRC37A copies: core duplicon genes acquired novel promoters and uniquely expanded in primates with unclear gene function, presumably cellular migration, chemotaxis, and immunity. 48 , 49 LRRC37A4P, A2, and A1 have been repeatedly shown to be associated with 17q21.31-inv 9 , 46 , 48 , 50 and have been demonstrated in fetal brains, 51 , 52 though with the cautioning that probes can bind to more than one target genes, especially using earlier array technology. 50 In short, the 17q.21.31-inv with balanced rearrangement does not drastically change gene dosage in the same way as do pathogenic CNVs but rather involves changes in a remarkably diverse range of gene regulatory activity, with downstream impact on normative variation in brain structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…LRRC37A shows lower expression in temporal and frontal cortex of individuals with H1 vs. H2 haplotype in populations with European ancestry (61), suggesting a possible protective effect. In fact, a recent study on Parkinson's disease linked protective sub-haplotypes of this locus with increased expression of LRRC37A in brain, although LRRC37A was primarily expressed in astrocytes in the substantia nigra (76). Although further work is needed to disentangle the effects of LRRC37A in neurons vs. astrocytes, and to see whether increased LRRC37A expression is likewise protective in other tauopathies, our results point to LRRC37A and ARL17B as important candidates for consideration in future studies of neurodegeneration.…”
Section: Discussionmentioning
confidence: 63%
“…For overall breast cancer risk, we also detect strong colocalization between eQTLs and GWAS signals at the 17q21.31 locus. This locus houses a large and common inversion polymorphism with associations with breast and ovarian cancer prognosis [94][95][96] , as well as widespread associations with multiple phenotypes, including neuropsychiatric traits, Parkinson's disease, and metabolic traits [97][98][99][100] . In particular, we found that the ncRNA KANSL1-AS1 potentially mediates distal-eQTLs of multiple pcGenes.…”
Section: Mediated Distal-eqtl Signal In Breast and Prostate Overlaps ...mentioning
confidence: 99%